Penetrating craniocerebral injuries in a civilian population in mid-Europe - Vajkoczy, Peter; Schürer, Ludwig; Münch, Elke; Schmiedek, Peter (Clinical neurology and neurosurgery, 1999)
Our current neurosurgical understanding of civilian penetrating craniocerebral injuries is based on US metropolitan series. It is unknown whether all principles applied to these patients are relevant in the Mid-European setting with its distinct epidemiology. The objective of this study was to characterize our patients with penetrating craniocerebral injuries, to analyze their outcome, and to identify relevant prognostic factors. Thirty-two patients with penetrating craniocerebral injuries were entered into the study. Patient evaluation comprised neurological, laboratory and radiographic analyses. Motivating factors were suicide (75%), assault (13%), and accident (9%). Initial GCS score, coagulopathy on admission, and radiographic extent of injury could be identified as outcome predictors (P<0.001). An aggressive therapeutic approach to patients with GCS 3-7 reduced mortality when compared to a conservative management (67 vs. 91%). Due to major differences in epidemiology and outcome of our penetrating craniocerebral injury patients when compared to major US metropolitan series, current therapeutic strategies applied to this patient population in mid-Europe should be reconsidered. The results of our study justify an aggressive neurosurgical approach even in those patients that are thought to have a deleterious prognosis. Predictive variables identified in this study and a novel CT-grading algorithm may help in decision making.